1999
DOI: 10.1002/(sici)1097-4628(19990404)72:1<41::aid-app4>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Surface reaction on polyvinylidenefluoride (PVDF) irradiated by low energy ion beam in reactive gas environment

Abstract: Polyvinylidenefluoride (PVDF) was irradiated by a keV Ar ϩ ion in O 2 environment for improving adhesion between PVDF and Pt, and reaction between PVDF and the ion beam has been investigated by X-ray photoelectron spectroscopy (XPS). The adhesion test between Pt and the modified PVDF was carried out by boiling test, in which the specimens were kept in boiling water for 4 h. Two failure modes (buckling up due to weak adhesion and crack formation due to strong adhesion) of Pt films have been observed in the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It should be noted that dc discharge treatment results in smaller contact angles and higher adhesion works and surface energies than other known methods of polyfluoroolefin modifications [1][2][3][4][5][6][7][8][9]25].…”
Section: Surface Modification Of Polyfluoroolefin Filmsmentioning
confidence: 92%
See 2 more Smart Citations
“…It should be noted that dc discharge treatment results in smaller contact angles and higher adhesion works and surface energies than other known methods of polyfluoroolefin modifications [1][2][3][4][5][6][7][8][9]25].…”
Section: Surface Modification Of Polyfluoroolefin Filmsmentioning
confidence: 92%
“…treatment on the anode [9]; similar results were also obtained with F4MB and F50. With PVDF films lower θ values were obtained on their treatment on the cathode [20]; the same was the case with F62 and F40.…”
Section: Surface Modification Of Polyfluoroolefin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advances, there are obstacles preventing the use of PPy as an electrode material for PVDF, such as the weak adhesion force between the PVDF and PPy. PVDF is a fluorocarbon material with a very low surface energy that adheres poorly to other materials [20,21,22,23]. It has also been reported that the adhesion force between the PPy and hydrophobic surfaces is weak [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, modifications to improve the hydrophilicity are urgently required for preparing PVDF membranes with outstanding performance characteristics [1][2][3]. At present, the main modification methods focus on surface modification [4][5][6][7] and blending with hydrophilic components [8][9][10][11]. Among the various surface modification methods, smearing glycerol or surfactant has short-term modification effect and may lead to filtrates with high organic concentration.…”
Section: Introductionmentioning
confidence: 99%